2022
DOI: 10.1002/ijgo.14270
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of clinical and health system bottlenecks to implementing new WHO postpartum hemorrhage recommendations: Secondary data analysis of the Kenya Confidential Enquiry into Maternal Deaths 2014–2017

Abstract: ObjectiveTo describe maternal deaths from postpartum hemorrhage (PPH) in Kenya by secondary analysis of the Kenya Confidential Enquiry into Maternal Deaths (CEMD) database and clinical audit of a sample of those deaths, and to identify the perceived challenges to implementing country‐specific PPH guidelines.MethodsA retrospective descriptive study using the Kenyan CEMD database and anonymized maternal death records from 2014–2017. Eight standards from the Kenya National Guidelines for Quality Obstetric and Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…At present, healthcare providers predominantly rely on clinical expertise and nonspecific risk factors to identify high-risk pregnancies. Further, the International Federation of Gynecology and Obstetrics (FIGO) developed a PPH care pathway to integrate WHO PPH guidelines in Sub-Saharan African countries (29). These guidelines are primarily derived from expert opinion and clinical consensus lacking the ability to offer personalized risk predictions.…”
Section: Discussionmentioning
confidence: 99%
“…At present, healthcare providers predominantly rely on clinical expertise and nonspecific risk factors to identify high-risk pregnancies. Further, the International Federation of Gynecology and Obstetrics (FIGO) developed a PPH care pathway to integrate WHO PPH guidelines in Sub-Saharan African countries (29). These guidelines are primarily derived from expert opinion and clinical consensus lacking the ability to offer personalized risk predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Knight et al [49] reported a higher average rate of non-maternal deaths in the UK compared to developing countries. Previous studies [50,51] have also highlighted that in developed countries, indirect causes of maternal mortality, particularly non-obstetric complications, are more prevalent than direct causes. This has been attributed to the well-organized antenatal care programs in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies examined this group of causes and reported rates ranging from 4.1 to 66.6%. About 62% of maternal mortalities worldwide can be attributed to direct causes, with obstetric hemorrhages accounting for nearly half of them (about 27%) [50]. Postpartum hemorrhages are the most common cause of obstetric hemorrhages (72%) [51] accounting for about 25% of maternal deaths globally [52].…”
Section: Discussionmentioning
confidence: 99%
“…While several challenges have been reported with these programs -including a lack of support for the costs of referrals, challenges for patients trying to access the services to which they were entitled [25], and persistent socioeconomic disparities in access to care [26]-these changes have been associated with improvements in the continuity of care [26]. However, alongside these improvements, several studies have documented important gaps in the quality of maternity care in Kenya [27][28][29].…”
Section: Study Setting and Designmentioning
confidence: 99%